Perencanaan dan Simulasi Jaringan Small Cell Indoor Hotspots Studi Kasus di Gedung Vokasi Universitas Telkom - Toha Ardi Nugraha (Universitas Muhammadiyah Yogyakarta, 2017)
Poor signal in indoor celluler network is caused by attentuation of the building partition. In indoor areas, signal from base station transmitter cannot received perfectly in the receiver part. Therefore, this study discusses about planning of Indoor Hotspot (InH) using Small Cells technology case studi in Vocational Building Telkom University. From the network simulation, the transmit power of the entire antennas can cover each floor as well with received signal level greater than -80 dBm with SIR level has positive value above 0dB. The lowest floor, the average received signal power values is the best value compare with the others with received power about -40 dBm using 6 InHs. SIR best quality on the first floor of the building with the average received signal quality value of about -50 dBm using 7 InHs.